Some Decomposition Results for Information Evaluation - Demski, Joel S. (Journal of Accounting Research, 1970)
One purpose of an accounting system, or any information system, is to provide a set of signals designed to communicate descriptions of certain past phenomena believed to be decision relevant in the future.' However, it is difficult to evaluate a given or proposed information system because of its complexity. This complexity arises in part because of the interrelated problems of which phenomena to describe and how best to describe them. Since complexity hinders information system evaluation, decomposition of the total interrelated system into a number of less complex subsystems for evaluation purposes is often desirable. Unfortunately, most decomposition will introduce errors into the analysis. But if we can predict the resultant errors, decomposition can still provide a useful surrogate evaluation method. The purpose of this paper is to explore the decomposition approach to information system evaluation, at the conceptual level, relying heavily on Feltham's recently proposed model for predicting the value of information in the single decision case.2